Bloodless "atonement": an exegetical, ritual, and theological analysis of Leviticus 5:11–13 - Peres, Caio (The journal of Hebrew scriptures, 2020)
According to Leviticus 5:11–13, semolina has the same ritual effect as blood. A thorough exegetical and ritual comparison between the חטאת of animals and the חטאת of semolina, or the מנחה-like חטאת, explains how this was possible. The results of this comparison are helpful in establishing the ritual effect of כפר as a process that defines the Priestly theology of the cult. According to Leviticus 5:11–13, semolina has the same ritual effect as blood. A thorough exegetical and ritual comparison between the חטאת of animals and the חטאת of semolina, or the מנחה-like חטאת, explains how this was possible. The results of this comparison are helpful in establishing the ritual effect of כפר as a process that defines the Priestly theology of the cult.